Kajian Penggunaan Kuasa Direksi Dalam Pelaksanaan Pengadaan Barang dan Jasa Dari Perspektif Hukum - Elsa febriani; Ali Abdullah (Universitas Djuanda, 2025)
The purpose of this study is how the legal aspects of the use of the power of directors in the procurement of services and goods and how the legal accountability in the use of the power of directors in the procurement of services and goods. The researcher examines the use of the power of directors associated with the case of the Company's borrowing and lending practice with the Directors' Power of Attorney Deed to participate in the Auction for the Construction of the Weda Islamic Boarding School Dormitory. This study uses the Case Approach Method which refers to the case of Decision Decision No. 9 / Pid.Sus-TPK / 2021 / PN Tte and the Statutory Regulation Approach. The data collection technique for this study uses the Library Study Technique. The data analysis technique used in this study is the Qualitative Analysis Technique with the Descriptive Analysis Method. The granting of a power of attorney by the Directors in the procurement of government services and goods that is not in line with statutory provisions causes the benefits of granting the power of attorney to be null and void by law. The responsibility of the Directors' power of attorney for the Company's borrowing and lending if it is proven that there has been a loss either to the Company or to the state, then the directors' power of attorney must be responsible for their actions personally.